An Unusual Localization of a Pleomorphic Adenoma in the Rhinopharynx - Fabio Pagella; Francesco Chu; Alessandro Pusateri; Elina Matti (Case Reports in Medicine)
Pleomorphic adenoma is the most common benign tumor of the parotid glands. Rarely it may arise from minor salivary glands of the upper aerodigestive tract. A 57-year-old woman was admitted at our institution presenting with nasal obstruction. Endoscopic evaluation revealed a pedicled mass in the rhinopharynx. After radiological examination, we opted for a transnasal endoscopic-assisted excision of the mass under general anaesthesia. Histological evaluation deponed for pleomorphic adenoma with clear surgical margins. No endoscopic evidence of local recurrence has been shown after 48 months of followup. In the literature, few cases of pleomorphic adenoma arising in the rhinopharynx have been reported. The introduction of endoscopy, as shown by our experience, leads to important benefits in the identification, treatment, and followup of such rhinopharyngeal benign tumors.